Radioprotection of mouse hemopoiesis by dipyridamole and adenosine monophosphate in fractionated treatment - Pospísil, M; Hofer, M; Znojil, V; Vácha, J; Netíková, J; Holá, J (Radiation research, 1995)
The purpose of the studies reported here was to investigate the ability of the combined administration of dipyridamole and adenosine monophosphate, drugs known to elevate extracellular adenosine, to protect mice undergoing treatment with fractionated irradiation (five doses of 2 or 3 Gy each) given at 24-h intervals. Based on observations of hemopoietic recovery (endogenous hemopoietic spleen colony formation, marrow granulocyte-macrophage colony-forming cells, peripheral blood cells) after the completion of fractionated irradiation and on survival studies, it was demonstrated that the repeated administration of the drugs 60 min before each of the radiation fractions mitigates the hemopoietic injury and enhances the survival of mice irradiated with an additional "top-up" dose. It could be deduced that the single protective actions of the drugs retain their efficacy in repeated treatment and enhance the sparing effect of dose fractionation on hemopoiesis. Interestingly, the toxic side effects of the drugs tend to decrease when they are administered repeatedly, probably due to the development of tolerance to their cardiovascular action. This reduction in toxicity offers benefit with respect to the potential use of these hemopoiesis-protecting drugs in clinical radiotherapy.
Keywords: dipyridamol; Mice, Inbred CBA; Hematopoiesis; Male; slezina; Survival Rate; Adenosine Monophosphate; mužské pohlaví; Spleen; Dipyridamole; Animals; adenosinmonofosfát; zvířata; hematopoéza; myši inbrední C57BL; myši; Mice, Inbred C57BL; Mice; Radiation-Protective Agents; radioprotektivní látky; myši inbrední CBA; míra přežití